Comparative Study of Length and Diameter of Umbilical Cord in Normal Vs Gestational Hypertensive cases in a Tertiary Care Hospital in Eastern Nepal - Yadav, Subodh Kumar; Yadav, Renu; Karn, Abhishek; Adhikari, Rakesh Kumar (Journal of Universal College of Medical Sciences, 2019)
INTRODUCTION :- The well being of the fetus and hence the baby is influenced by a number of factors among which the length and diameter of umbilical cord is one important aspect. Studies have found association between gestational hypertension and the structure of umbilical cord. The objective of this study was to determine the effects of gestational hypertension on the length and diameter of umbilical cord. MATERIAL AND METHODS :- A total of 70 umbilical cords with placenta were collected in Nobel Medical College and Teaching Hospital for comparison of umbilical cords length and diameter between normotensives and patients with gestational hypertension. Data were statistically analyzed. RESULTS :- The difference in umbilical cords' diameter was statistically significant between normotensives and patients with gestational hypertension whereas the length of the umbilical cord had no statistically significant difference. CONCLUSION :- We concluded that gestational hypertension affects the diameter of umbilical cord by decreasing it significantly which may affect normal fetal development.